Fungsi Kesenian Kompangan Dalam Pesta Perkawinan Masyarakat Kampung Baru Kelurahan Bajubang Kabupaten Batanghari Provinsi Jambi - Rahmi Fajriah; Wimbrayardi Wimbrayardi (FBS Universitas Negeri Padang, 2020)
This research is a qualitative research with descriptive analysis method. The data collection started from data existing in the field - from the results of observations, interviews, field notes, and study documentation. Then, the data were analyzed by using data reduction techniques, data presentation, and drawing conclusions. This research is based on Alan P. Merriam's (1964: 219-226) theory about 10 musical functions.The results of this study indicate that Kompangan Art is used in various traditional events. It firstly used in a wedding party. Along with the development of time, Kompangan Art is also used in child shaving and circumcision events as an entertainment for the guests who come to the event. The art of Kompangan music plays an important role for the community, especially in marriage parties. It is due to the fact that it is played as the groom's pageant music. From these uses, the reactions that occur in community activities can be seen. It relates to the function through the feelings that humans feel when they see and hear the art. The functions found are the function of (1) emotional expression; (2) Entertainment; (3) Communication; and (4) the continuity of cultural norms.